Dimorfisme Seksual, Reproduksi dan Mangsa Kadal Ekor Panjang Takydromus sexlineatus Daudin, 1802 (Lacertilia :Lacertidae) - Mumpuni, Mumpuni (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTSexual Dimorphism, Reproduction and Prey of Long Tailed Lizard Takydromus sexlineatusDaudin, 1802 (Lacertilia :Lacertidae). The morphology and reproductive biology of Takydromussexlineatus were studied in Bogor. Males are larger than females. There is sexual dimorphism onhead size and tail length (larger and longer tail on males) of body size among sexually matureadults, apparently as a consequence of sexual selection. The diet of T. sexlineatus consists ofvariety of insects and their larvae, arachnids, decapods and snails. Most of the diet are insect(more than 70 % for adults and juveniles). There are higher prey competitions at adult skinksbetween males and females, adult females and juveniles, but not between adult males andjuveniles. The length of adult males and females are 44.6 - 58.1 mm and 49.6 - 62.3 mm respectively,lay eggs throughout the year with 2 -3 clutches, per clutch consists of 1 - 3 eggs.Key words: Lizard, Takydromus, Ecology, Sexual Dimorphism, Prey, Reproduction, Bogor, Indonesia